Mechanistic studies on Diels-Alder [4þ2] cycloaddition reactions ofa,b-substituted cyclobutenones: Role of substituents in regio- andstereoselectivity - Fosu, Evans; Tia, Richard; Adei, Evans (Elsevier Ltd., 2020)
An article published by Elsevier Ltd and also available at http://dx.doi.org/10.1016/j.tet.2016.10.063